2022
DOI: 10.1002/tox.23690
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A (BPA) induces apoptosis of mouse Leydig cells via oxidative stress

Abstract: As one of the most frequently produced synthetic compounds worldwide, bisphenol A (BPA) has been widely used in many kinds of products such as appliances, housewares, and beverage cans. BPA has been shown to cause damage to male reproductive system; however, the potential mechanism remains to be investigated. In the present study, BPA exposure decreased the testis and epididymis coefficient, caused a disintegration of germinal epithelium, decreased the density and motility of sperm in the epididymis tissue, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…54,55 The evidences have demonstrated that inflammation was closely related with the XOD and disorders of PUFA. 56,57 Excitingly, AAEO could reverse the disturbance of purine metabolism by reducing the activity of XOD, and significantly reduce oxidative stress and the inflammatory responses in liver tissues by increasing the mRNA expressions of SOD and CAT in mice liver tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 The evidences have demonstrated that inflammation was closely related with the XOD and disorders of PUFA. 56,57 Excitingly, AAEO could reverse the disturbance of purine metabolism by reducing the activity of XOD, and significantly reduce oxidative stress and the inflammatory responses in liver tissues by increasing the mRNA expressions of SOD and CAT in mice liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, XOD generated a large amount of ROS in the process of catalyzing hypoxanthine and xanthine to produce uric acid, which caused severe oxidative stress‐induced hepatotoxicity 54,55 . The evidences have demonstrated that inflammation was closely related with the XOD and disorders of PUFA 56,57 . Excitingly, AAEO could reverse the disturbance of purine metabolism by reducing the activity of XOD, and significantly reduce oxidative stress and the inflammatory responses in liver tissues by increasing the mRNA expressions of SOD and CAT in mice liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells in mammalian testicular tissue can synthesize and secrete testosterone, and high levels of testosterone are necessary for normal spermatogenesis ( Chung et al, 2020 ). BPA reduces the expression of Leydig cell steroidogenic enzymes, including StAR, CYP11A1, CYP17A1, and 17β-HSD, thereby impacting testosterone synthesis and secretion ( Zhang et al, 2023 ). Cholesterol is the precursor for testosterone synthesis, and it is transported by StAR to the inner mitochondrial membrane ( Stocco, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BPA-treated rat and human stem cells have a significant decrease in cell viability and substantial apoptosis as early as 10 min of exposure and at physiologically relevant low doses [ 44 ]. At the same time, it was found that BPA induced apoptosis of mouse interstitial cells through oxidative stress [ 45 ]. Treatment with Se significantly alleviated Cd-induced apoptosis in chicken livers, as evidenced by a reduction in the production of NO, iNOS activity, the number of apoptotic cells, and mRNA and protein expression levels of caspase-3 and Bax [ 46 ].…”
Section: Discussionmentioning
confidence: 99%